Felony Prosecution and Sentencing in North Carolina, 1981-1982 - Clarke, Stevens H. ([Verlag nicht ermittelbar], 1985)
This survey assesses the impact of a determinant sentencing law, the Fair Sentencing Act, which became effective July 1, 1981, in North Carolina. Specific variables include information from official court records on witness testimony and quality of evidence, information from prison staff and probation/parole officers, and social, demographic, and criminal history for defendants. In this dataset it is also possible to trace defendants through the criminal justice system from arrest to disposition.